2011
DOI: 10.1029/2010jc006490
|View full text |Cite
|
Sign up to set email alerts
|

Interannual modulation and its dynamics of the mesoscale eddy variability in the southeastern tropical Indian Ocean

Abstract: [1] Interannual modulation of the mesoscale eddy activity at the intraseasonal time scale in the southeastern tropical Indian Ocean (SETIO) and a possible mechanism responsible for the modulation are investigated using the results from a high-resolution oceanic general circulation model (OGCM). The model reproduces reasonably well the observed intraseasonal variability in the SETIO and its interannual modulation. It is shown that the simulated intraseasonal eddies are generated by baroclinic instability. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Additionally, both were long‐lived, at ~240 days for the January 2004 feature (Figure (c)) and > 240 days for the April 2009 feature (Figure (d)). The wavelengths and intraseasonal periods are consistent with observed and model simulated instabilities associated with the South Equatorial Current in these latitudinal regions noted by previous studies (e.g., Feng & Wijffels, ; Ogata & Masumoto, , ; Trenary & Han, ; Yu & Potemra, ). Other studies (see, e.g., Chelton et al, ) have noted that oceanic eddies associated with instabilities propagate with similar phase speeds to Rossby waves.…”
Section: Resultssupporting
confidence: 90%
“…Additionally, both were long‐lived, at ~240 days for the January 2004 feature (Figure (c)) and > 240 days for the April 2009 feature (Figure (d)). The wavelengths and intraseasonal periods are consistent with observed and model simulated instabilities associated with the South Equatorial Current in these latitudinal regions noted by previous studies (e.g., Feng & Wijffels, ; Ogata & Masumoto, , ; Trenary & Han, ; Yu & Potemra, ). Other studies (see, e.g., Chelton et al, ) have noted that oceanic eddies associated with instabilities propagate with similar phase speeds to Rossby waves.…”
Section: Resultssupporting
confidence: 90%
“…Mesoscale eddies play a critical role in the ocean circulation through mass and heat transport (Chelton, 2013;Dong et al, 2014;Zhang et al, 2014). Barotropic and baroclinic instabilities are the main source of eddy generation (Ogata & Masumoto, 2011). The barotropic instability converts kinetic energy of mean flows to eddy energy, and the baroclinic instability converts potential energy of mean flows to eddy energy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the oceanic variability forced by atmospheric forcing fields at the surface and from the ITF, oceanic variability can also arise from internal variability due to nonlinearity of the oceanic system. Previous studies reported the effects of oceanic internal variability in generating “intraseasonal timescale” variability near the Somali coast, in the southwest tropical basin, and the South Equatorial Current region of the Indian Ocean [e.g., Kindle and Thompson , ; Woodberry et al ., ; Tsai et al ., ; Jochum and Murtugudde , ; Feng and Wijffels , ; Yu and Potemra , ; Han et al ., ; Palastanga et al ., ; Ogata and Masumoto , , ; Trenary and Han , ]. Levels of high eddy kinetic energy found in the 20°S–30°S band of the South Indian Ocean undergo large seasonal and interannual variations, resulting from varying vertical shear of the South Indian Counter Current‐South Equatorial Current system [e.g., de Ruijter et al ., ; Palastanga et al ., ; Jia et al ., , ].…”
Section: Introductionmentioning
confidence: 99%